Ethics and action. - Winch, Peter (London, Routledge and Kegan Paul, 1972)
Ten essays about interrelated moral issues.
Understanding a primitive society -- Nature and convention -- Human nature -- Man and society in Hobbes and Rousseau -- Wittgenstein's treatment of the will -- Trying -- The universalizability of moral judgments -- Moral integrity -- Can a good man be harmed? -- Ethical reward and punishment -- Index.
Includes bibliographical references.
Keywords: Ethics